FIGURE 3 in A new species of Sphaerodoridium Lützen, 1961 from Iceland (Polychaeta: Sphaerodoridae) - Moreira, Juan; Parapar, Julio (Zenodo, 2015)
FIGURE 3. Sphaerodoridium guerritai sp. nov. Holotype IINH 33095. A, parapodium 1, dorsal view; B, parapodium 1, ventral view (detail: distal end of ventral cirrus); C, parapodium 3, dorsal view; D, parapodium 3, ventral view; E, parapodium 4, dorsal view; F, parapodium 4, ventral view; G, parapodium 5, dorsal view, discontinuous line showing position of acicula; H, parapodium 5, ventral view; I, parapodium 12, dorsal view. All parapodia from the right side of the body. Published as part of Moreira, Juan & Parapar, Julio, 2015, A new species of Sphaerodoridium Lützen, 1961 from Iceland (Polychaeta: Sphaerodoridae), pp. 91-105 in Zootaxa 3911 (1) on page 96, DOI:10.11646/zootaxa.3911.1.5, http://zenodo.org/record/236683